Results of a study of the ammonia absorption efficiency by a brinе in a vortex device - Hrubnik, A.; Novozhylova, T.; Semenov, Evgeny (Scientific Route OÜ, Estonia, 2020)
Object of research: vortex mass transfer device for the effective absorption of ammonia by brine in soda production. Investigated problem: intensification of mass transfer processes and ensuring effective absorption of ammonia with small dimensions of the device and low hydraulic resistance. Main scientific results: studies of ammonia absorption efficiency in a laboratory device are carried out, which confirm the operability of the proposed device design. The dependences of the efficiency of the vortex device on the ammonia concentration and the brine consumption are revealed. The flow velocity and pressure in the device are simulated at various capacities. Scope of practical use of the research results: the research results can be used in the design of mass transfer equipment, primarily equipment for purifying emissions from ammonia and gas breakers from soda ash columns. Innovative technological product: the design of the vortex device, which allows achieving a high degree of absorption in ammonia with a concentration of up to 130 g/m3 of the order of 99 % at low operational (due to low hydraulic resistance) and capital (due to the compactness and small size of the installation) costs. Scope of the innovative technological product: the vortex device of the proposed design can be used to clean emissions, absorption of ammonia vapor or other mass transfer processes.

Об'єкт дослідження: вихровий масообмінний пристрій для ефективного поглинання аміаку розсолом в содовому виробництві. Досліджена проблема: інтенсифікація процесів масообміну і забезпечення ефективної абсорбції аміаку при малих габаритах пристрою і низькому гідравлічному опорі. Основні наукові результати: вивчена ефективність поглинання аміаку в лабораторній установці, які підтверджують працездатність запропонованої конструкції пристрою. Виявлено залежності ККД вихрового пристрою від концентрації аміаку і витрати розсолу. Швидкість потоку і тиск в пристрої моделюються при різних потужностях. Сфера практичного використання результатів дослідження: результати досліджень можуть бути використані при проектуванні массообменного обладнання, в першу чергу обладнання для очищення викидів від аміаку і газових викидів з колон кальцинованої соди. Інноваційний технологічний продукт: конструкція вихрового пристрою, що дозволяє домогтися високого ступеня поглинання аміаку з концентрацією до 130 г / м3 близько 99% при низьких експлуатаційних (через низький гідравлічного опору) і капітальних (через компактності) і невеликий розмір установки) витрат. Сфера застосування інноваційного технологічного продукту: вихровий пристрій пропонованої конструкції може використовуватися для очищення викидів, абсорбції парів аміаку або інших масообмінних процесів.
Keywords: vortex device; ammonia absorption; carbonization stage emissions; swirler; flow modeling; вихровий пристрій; абсорбція аміаку; викиди на стадії карбонізації; завихрення; потокове моделювання